Vitrification of immature oocytes of goats in Bangladesh (Bangladesh Veterinarian, 2019)
Cryopreservation of oocytes and embryos by vitrification can have advantages in assisted reproductive technologies (ARTs) in mammals. The aim of this study was to establish an effective vitrification procedure and cryodevice for goat’s oocytes in Bangladesh. Cumulus oocyte complexes (COCs) were collected from ovaries from slaughterhouse. COCs with more than 3 layers of cumulus cells were selected. COCs were vitrified by two-step procedure using 7.5% and 15% dimethyl sulphoxide (DMSO) as cryoprotective agent (CPA), loaded on Cryotop or French mini-straw, then directly plunged into liquid nitrogen (LN2). Then the COCs containing Cryotop or French mini-straws were warmed in 0.25 M sucrose and 20% FBS-supplemented tissue culture medium (TCM) 199 followed by in vitro culture in 50 μl droplets of bicarbonate-buffered TCM 199 supplemented with 10% FBS, pyruvate, FSH and oestradiol for 24 h at 39°C with 5% CO2 in humidified air. After maturation culture, oocytes were denuded and examined under inverted microscope for presence of polar body as the indication of maturation. The in vitro maturation rate of goat’s oocytes after vitrification and warming was 39.3 ± 6.8%, 31.3 ± 9.4%, 61.6 ± 14.2% when using Cryotop (cryodevice), French mini-straws and without vitrification (control), respectively. Maturation rate was significantly higher (P